2000
DOI: 10.1111/1467-8292.00151
|View full text |Cite
|
Sign up to set email alerts
|

The Co‐operative Advantage

Abstract: IntroductionThe international trend to demutualise ¢nancial services (mutuals and co-operatives), the conversions of farmer co-operatives in many countries, and the well published bid by Lanica to takeover the UK 's largest consumer co-operative, have contributed to a public perception that the co-operative idea is one that belongs to a past generation.Published research and general statistics in annual reports in various sectors of the co-operative movement indicate that although there are signs of growth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 1 publication
1
87
0
10
Order By: Relevance
“…at the neighborhood level (Degli Antoni and Portale 2011;Evers 2001;Gonzales 2007;Pestoff 2009;Putnam 2000). It can even create positive spillover effects on the local and regional economy and civil society (Putnam 1993;Spear 2000).…”
Section: Social Capital In the Context Of Cooperative Organizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…at the neighborhood level (Degli Antoni and Portale 2011;Evers 2001;Gonzales 2007;Pestoff 2009;Putnam 2000). It can even create positive spillover effects on the local and regional economy and civil society (Putnam 1993;Spear 2000).…”
Section: Social Capital In the Context Of Cooperative Organizationsmentioning
confidence: 99%
“…Therefore, founding and maintaining a cooperative requires a group of potential members who would be able to provide the organization with resources which they would access and mobilize through social ties. Thus, cooperatives, in contrast to for-profit organizations, can be seen as organizations that mainly build on the social capital of all their members, who are highly committed to a common goal, as their key resource (Spear 2000;Valentinov 2004). Even in for-profit enterprises, social capital can exist to a certain degree with the benefit of reducing transaction costs (Laville and Nyssens 2001).…”
Section: Social Capital In the Context Of Cooperative Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it has been shown that cooperatives are generally perceived as trustworthy, given their constraint on the profits distribution and their democratic governance (Hansmann 1996;Ole Borgen 2001). In addition, citizen ownership contributes to the trust capital of CBE initiatives and cooperatives as it provides the guarantee to non-controlling stakeholders that the firm is managed by people who share their interest (Spear 2000). This is consistent with the findings that horizontal networks, where people have equivalent status and power, engender trust because they facilitate exchanges of information and face-to-face communication, whereas hierarchies tend to inhibit information flows due to asymmetric power relationships (Kasperson et al 1999).…”
Section: Community-based Energy Initiatives and Institutional Resiliencementioning
confidence: 99%
“…This is necessary in order to go beyond the empty rhetoric of terms such as 'partnership', 'collaboration' and 'co-operation', and understand how these complex forms of organising are built and maintained (Atkinson, 1999;Hastings, 1996). There has been much discussion on the need for collaboration (OTS, 2009) and co-operation between organisations is given as a core value of some forms of social enterprises such as co-operatives (Spear, 2000) but very little work has been carried out on understanding the process of building these relationships. This chapter examines the context of collaboration with the state for public services, reviews the literature on collaboration and social enterprise, and draws on the literature of interorganisational relationships to present a framework for understanding how collaboration is built and maintained.…”
Section: Introductionmentioning
confidence: 99%